KAJIAN SUHU REAKSI TERHADAP POLA SUBSTITUSI DAN HASIL SINTESIS DERIVAT KUERSETIN - Aini, Nur; Fauzi, Muhammad; Su’aida, Nily (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Quercetin is a flavonoid compound with various pharmacological activities but has limited solubility and stability. The derivatization synthesis of quercetin through acylation with benzoyl chloride was carried out at temperatures of 25°C, 40°C, and 60°C using acetone as the solvent and pyridine as the catalyst. The reflux reaction for 12 hours produced mono-benzoylation characterized by Thin Layer Chromatography (TLC), column chromatography, as well as UV-Vis and IR spectra confirming the presence of benzoyl groups on quercetin. The 60°C temperature resulted in multi-benzoylation substitution, indicated by two carbonyl bands at 1785.00 cm⁻¹ and 1742.36 cm⁻¹, along with the highest yield of 88%. Controlling the reaction temperature can direct a more selective substitution pattern and improve the efficiency of quercetin derivatization. Higher temperatures accelerate the reaction rate and promote multi-substitution, potentially affecting the biological activity of the product.